Familial guidance and the provided services to family according to cognitive behavioural and psychological guidance strategies - Hedidane, Khadra (Journal of Human Sciences, 2023)
Guidance looks for helping individuals, in all ages, to surpass their psychological and social problems, which prevent them from being normal persons. This is done through using several ways.  Familial guidance, like all the other types of guidance, looks for achieving this objective. It looks for helping the family members to work as a team, and contribute to eliminate tension resulted from various familial problems threatening this unity entity, which would lead to the familial disillusion and serious problems with serious results threatening individual and society.  Familial guidance has several strategies enabling it to achieve these objectives including cognitive behavioural and psychological guidance strategies.  What’s the familial guidance? What’re cognitive behavioural and psychological guidance strategies?